Nutrition in congenital heart disease: consensus document - Fernando Centeno-Malfaz; Ana Moráis-López; Ana Caro-Barri; Luis Peña-Quintana; Nuria Gil-Villanueva; Susana Redecillas-Ferreiro; Sonia Marcos-Alonso; Ignacio Ros-Arnal; María Ángeles Tejero; César Sánchez Sánchez; Rosaura Leis (Anales de Pediatría (English Edition), 2023)
Introduction: The prevalence of malnutrition among infants with congenital heart disease (CHD) is high. Early nutritional assessment and intervention contribute significantly to its treatment and improve outcomes. Our objective was to develop a consensus document for the nutritional assessment and management of infants with CHD. Material and methods: We employed a modified Delphi technique. Based on the literature and clinical experience, a scientific committee prepared a list of statements that addressed the referral to paediatric nutrition units (PNUs), assessment, and nutritional management of infants with CHD. Specialists in paediatric cardiology and paediatric gastroenterology and nutrition evaluated the questionnaire in 2 rounds. Results: Thirty-two specialists participated. After two evaluation rounds, a consensus was reached for 150 out of 185 items (81%). Cardiac pathologies associated with a low and high nutritional risk and associated cardiac or extracardiac factors that carry a high nutritional risk were identified. The committee developed recommendations for assessment and follow-up by nutrition units and for the calculation of nutritional requirements, the type of nutrition and the route of administration. Particular attention was devoted to the need for intensive nutrition therapy in the preoperative period, the follow-up by the PNU during the postoperative period of patients who required preoperative nutritional care, and reassessment by the cardiologist in the case nutrition goals are not achieved. Conclusions: These recommendations can be helpful for the early detection and referral of vulnerable patients, their evaluation and nutritional management and improving the prognosis of their CHD. Resumen: Introducción: La tasa de desnutrición entre los lactantes con cardiopatías congénitas (CC) es elevada. Una evaluación e intervención nutricional tempranas ayudan a su tratamiento y mejoran el pronóstico. El objetivo fue elaborar un documento de consenso para la evaluación y el tratamiento nutricional del lactante con CC. Material y Métodos: Se utilizó una técnica Delphi modificada. En base a la literatura y a su experiencia clínica, un comité científico elaboró un listado de afirmaciones que abordaban la derivación a Unidades de Nutrición Pediátrica (UNP), la evaluación y el manejo nutricional de los lactantes con CC. Especialistas en cardiología pediátrica, y gastroenterología y nutrición pediátrica evaluaron el cuestionario en 2 rondas. Resultados: Participaron 32 especialistas. Tras dos rondas de evaluación, se consensuaron 150 de 185 ítems (81%). Se determinaron patologías cardiacas de bajo y alto riesgo nutricional y factores asociados cardíacos o extracardíacos que confieren riesgo nutricional alto. Se elaboraron recomendaciones para la evaluación y seguimiento en unidades de nutrición y sobre el cálculo de los requerimientos nutricionales, el tipo de nutrición y la vía de administración. Se enfatiza la necesidad de un tratamiento nutricional intensivo en el preoperatorio, del seguimiento por la UNP en el postoperatorio cuando se haya necesitado intervención preoperatoria, y de la reevaluación por el cardiólogo cuando no se alcancen los objetivos nutricionales. Conclusiones: Estas recomendaciones pueden ser de ayuda para la detección precoz y derivación temprana de población vulnerable, su evaluación y tratamiento nutricional y para mejorar el pronóstico de su CC.